2009
DOI: 10.1007/s00213-009-1734-x
|View full text |Cite
|
Sign up to set email alerts
|

Central administration of p-hydroxyamphetamine produces a behavioral stimulant effect in rodents: evidence for the involvement of dopaminergic systems

Abstract: These data suggest that dopaminergic systems in the NAc may play important roles in p-OHA-induced locomotor activity in rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Other studies have reported that direct injection of Amph into the NAc is sufficient to induce a sensitized response in rats previously chronically injected with psychostimulants, suggesting that the NAc is involved in the induction of behavioral sensitization [5,14,53,56]. More recent studies reported increased locomotor activity following microinjections of p-hydroxyamphetamine directly into the NAc [51]. Although several studies purport that behavioral sensitization originates in the VTA while expression occurs in the NAc, the above observations along with our own suggest that the NAc is also involved in the induction of behavioral sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that direct injection of Amph into the NAc is sufficient to induce a sensitized response in rats previously chronically injected with psychostimulants, suggesting that the NAc is involved in the induction of behavioral sensitization [5,14,53,56]. More recent studies reported increased locomotor activity following microinjections of p-hydroxyamphetamine directly into the NAc [51]. Although several studies purport that behavioral sensitization originates in the VTA while expression occurs in the NAc, the above observations along with our own suggest that the NAc is also involved in the induction of behavioral sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a misconception by practitioners of the glymphatic theory that molecules injected ICV or CM in awake animals do not circulate, penetrate the parenchyma, and clear. There are numerous studies dating back decades showing psychostimulants, peptides, and neurotransmitters have immediate effects-within minutes-on nociception, gastric motility, heart rate, blood pressure, urine volume, hormone secretion and behavior following ICV injection (for examples see Pedigo et al, 1975;Hall, 1981;Berkowitz and Sherman, 1982;Cowan et al, 1985;Tsukamura et al, 2000;Hanada et al, 2001;Stone et al, 2003;Barcia and Gallego, 2009;Onogi et al, 2010;Toll et al, 2012). Radiolabeled peptides spread across the parenchyma hitting their target receptors and peaking within 2-5 min after ICV injection and almost immediately appear in the systemic blood (Saija et al, 1989).…”
Section: The Confound Of Anesthesiamentioning
confidence: 99%